The effectiveness of audiovisual translation as a teaching tool for secondary school students in Singapore – a case study of two L2 Chinese language learning groups - Fang, Yu (Nanyang Technological University, 2023)
This paper takes on the assumption that Chinese language students in Singapore mainstream schools are primarily English-speaking, with Mandarin as their second language at home. The assumption leads to the attempt to explore whether the use of the English language would supplement and support the learning of the L2 Chinese language in the form of translation pedagogies. The case study examines the extent to which audiovisual translation as a learning resource help L2 Chinese language learners enhance their vocabulary. Research procedures involved conducting translation workshop sessions, where student participants developed translations of audiovisual materials. They were assessed in a series of pre, mid and post-course assessments to track the extent of their improvement. Following the comparison, various factors were examined to determine if learners' proficiency in Chinese and English would affect the extent to which translation lessons help them acquire new vocabulary. Audiovisual translation was partially proven as an effective teaching strategy for L2 Chinese language learners. The difference in participant scores from pre to post-course indicated that most participants achieved some form of improvement, albeit with a vast range of improvement margins. Participants with lower base scores tended to experience more improvement in their translation in the post-course assessment. Some participants with high language proficiency either had little value-add or demonstrated low receptivity towards the content taught. The study's outcomes suggest that educators take on differentiated pedagogies to meet the different needs of language learners at their respective levels of language proficiency. Keywords: translation, bilingualism, second language acquisition, translanguaging pedagogy, L2 vocabulary